2019
DOI: 10.1371/journal.pone.0222545
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for increasing diagnostic yield of community-onset bacteraemia within the emergency department: A retrospective study

Abstract: Bloodstream infections (BSI) are associated with high mortality. Therefore, reliable methods of detection are of paramount importance. Efficient strategies to improve diagnostic yield of bacteraemia within the emergency department (ED) are needed. We conducted a retrospective analysis of all ED encounters in a high-volume, city-centre university hospital within Germany during a five-year study period from October 2013 to September 2018. A time-series analysis was conducted for all ED encounters in which blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Major indications for ED physicians to suspect infection, obtain BCs [36], and consider antimicrobial therapy include the following: clinically suspected organ infection with accompanying bacteraemia (such as meningitis, cholecystitis, pyelonephritis, necrotising fasciitis, osteomyelitis, severe pneumonia, endocarditis, vascular graft infection, or prosthetic joint infection), clinically suspected sepsis, defined by published sepsis scores, such as the sepsis-related organ failure assessment score, quickSOFA (qSOFA) [22] or SIRS criteria [37], or detected or reported body core temperature ≥ 38.3 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Major indications for ED physicians to suspect infection, obtain BCs [36], and consider antimicrobial therapy include the following: clinically suspected organ infection with accompanying bacteraemia (such as meningitis, cholecystitis, pyelonephritis, necrotising fasciitis, osteomyelitis, severe pneumonia, endocarditis, vascular graft infection, or prosthetic joint infection), clinically suspected sepsis, defined by published sepsis scores, such as the sepsis-related organ failure assessment score, quickSOFA (qSOFA) [22] or SIRS criteria [37], or detected or reported body core temperature ≥ 38.3 °C.…”
Section: Methodsmentioning
confidence: 99%
“…5 Most guidelines recommend to obtain two to three BC sets over a 24-h period for the optimal detection of BSIs. 3,6,16 Although the isolation rate increases with multiple sampling; the financial and ethical restrictions make this strategy difficult to implement, especially in LMICs and public sector facilities catering to poor people. 7 With the advent of newer CMBCS such as BacT/ALERT VIRTUO, the isolation rate has been reported to be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature stated that the diagnostic yield of blood cultures significantly improves with the increase of the number of blood cultures drawn (67%, 80% and 96% with 1, 2 and 3 sets of BCs respectively). 3,6 However, implementing the practice of drawing multiple sets of BCs is extremely difficult, particularly in LMICs, which may be attributed to financial, manpower, ethical and infrastructure-related constraints. The situation is more difficult in public sector settings catering to poor people, where it is often observed that clinicians tend draw only one or two BC bottles, which results in a very poor organism isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a UBC strategy has not been evaluated in the intensive care unit (ICU) with the specific problem of a high incidence of fever during the ICU stay. Predicting a BSI in a febrile and critically ill patient (at admission or during ICU stay) is difficult, with only 10% of patients sampled having a BSI [ 1 , 2 , 16 ]. Changing a MS procedure for a UBC strategy without focusing on the ordering rule for BC collection would be associated with an important increase in the total number of collected BC bottles.…”
Section: Introductionmentioning
confidence: 99%